Gender Correlates on Knowledge, Skills, Competencies Gained From and Impact of a Graduate Degree - Pati-Blanco, Nenita (Jurnal Pendidikan Indonesia Gemilang, 2024)
The 2019 Philippine Statistics Authority report on education equality in the Philippines based on CHED data shows that more females were getting advanced degrees than males. This study aimed to determine the gender correlates on knowledge, skills, and competencies (KSC) gained and the impact of a graduate degree on the graduates of a College in Laoag City, Ilocos Norte, Philippines. Specifically, a comparison of the KSC gained, and the impact of their graduate degree on the personal lives and careers of male and female graduates was performed. Findings reveal no significant difference in the KSC gained and the impact of a graduate degree on the male and female graduates, except on interdisciplinary learning, with females being more knowledgeable in this area. In terms of effects, males experienced a higher impact on their graduate degrees than females in most areas of their personal lives and careers. However, statistically, such a difference was not significant. The researcher concluded that interdisciplinary learning is the only gender correlate for KSC and none for the impact of a graduate degree earned at a College in Laoag City, Ilocos Norte, Philippines. It is recommended that this study be replicated with more indicators for KSC and the impact and inclusion of other factors for the revised graduate school curricula.